ISLAMIC AND CULTURAL ACCULTURATION AS LOCAL WISDOM IN PROTECTING THE ENVIRONMENT OF MERAPI MOUNTAIN AREAS - Rizki Arumning Tyas (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2022)
The community around Mount Merapi with all its local wisdom believes that coexistence with Merapi requires norms and ethics. This research is a qualitative descriptive research with a literature review technique. This study aims to explore the concept of the beliefs of the Merapi people, the influence of Javanese Islam on the beliefs of the Merapi people, as well as the ethics of living the people around Merapi. Based on the results of the study, it is known that the concept of belief in the people on the slopes of Merapi is syncretism. The influence of Islamic teachings on the traditions of the Slopes of Merapi is the emergence of local people's understanding that combines Javanese traditions and Islamic teachings. In living, the Merapi community believes that with ethics in farming, raising livestock, living, and living, it can create harmony between the people on the slopes of Mount Merapi and the natural environment. The Merapi community continues to revive and preserve various traditions amid the onslaught of modernization currents, such as the wiwitan tradition, dawetan sapi, and becekan. This is one of the efforts to maintain a balance between humans and nature. Keywords: Islamic and Cultural Acculturation, Local Wisdom, Protecting Environment, Merapi Mountain Areas